Otolith shape analysis as a tool for stock separation of horse mackerel(Trachurus trachurus)in the Northeast Atlantic and Mediterranean - Stransky, Christoph; Murta, Alberto G.; Schlickeisen, Jürgen; Zimmermann, Christopher (Fisheries Research, 2008)
The geographic variability in otolith shape of horse mackerel (Trachurus trachurus) was investigated as a tool for stock separation. The outlines of several thousand otoliths, collected in 20 sampling areas during two consecutive years and covering most of the distributional range of the species in the Northeast Atlantic and Mediterranean, were digitised and analysed for shape variation by elliptical Fourier analysis. Only fish of a medium total length (20–35 cm) were included in the data analysis to minimise size effects between areas. The extracted Fourier descriptors were corrected for fish size preceding multivariate analysis. Multidimensional scaling of the average Fourier descriptors by area, combining both sampling years, showed three distinct clusters of areas: a northern, an Ibero-Mauritanian and an eastern Mediterranean group. These patterns were supported by discriminant analysis of the individual Fourier descriptors, with correct classifications ranging from 31 to 95%. Similar groups could be observed when analysing the two sampling years separately. The discrimination between these groups was 81–88%, while individuals from the Northeast Atlantic and Mediterranean were correctly classified by around 88–91%. Average otolith shapes for these groups showed characteristic differences, especially in the dorsal part of the otolith outline. The results of this study indicate that the separation line between the western and the southern stock should be shifted to the coast of southern Galicia (Cape Finisterre). In contrast to previous genetic and morphometric studies, the observed variation in otolith shapes could not confirm a separation of a western horse mackerel stock from the North Sea stock. Further, fish from the areas around the Iberian Peninsula (including the western Mediterranean) appear to be very similar to the northwest African occurrences. By integration of the inferred information on stock structure into a currently pursued multidisciplinary approach to stock identification of horse mackerel, ...